Diversity of orchid types in the Oeluan Tourism Forest, Bijeli Village, Noemuti District, North Central Timor Regency - Dewi, Ni Putu Yuni Astriani; Angket, Stefanus; Ledheng, Ludgardis; Sele, Yunawati; Welsiliana (Interdisciplinary International Journal of Conservation and Culture, 2024)
Indonesia as a mega biodiversity country has a variety of fauna and flora. One of the floras that is often found in Indonesia is orchids. Orchids have high economic value and are able to balance the ecosystem in their habitat. This study was aimed at determining the diversity of orchid species in the Oeluan tourism forest. The current study employed a quantitative descriptive study by using the transect and the purposive sampling method. The research was conducted in February at the Oeluan Tourism Forest. The results of this study indicated that there were four terrestrial orchid genera and three epiphytic orchid genera. The analysis of the diversity index of orchid species in the Oeluan tourism forest resulted in the diversity index of (H’) 1.0438 in the medium category. The measured environmental factors at the study site were an average soil pH of 7, an average humidity of 76.33% and an average air temperature of 27.400C. The diversity of orchid species in the Oeluan tourism forest, bijeli village, Noemuti district, North Central Timor regency, East Nusa Tenggara Province, was included in the medium category.